Estilos de afrontamiento en adultos que padecen de psoriasis en Lima Metropolitana - Fujiki Pereyra, Verónica Hikari (2016)
The present study aims to know the styles and coping strategies in adults with psoriasis in Metropolitan Lima. It also seeks to compare each style according to gender and the stage of development in which they are located. The participants were 80 persons of both sexes between 20 and 65 years old with the diagnosis of psoriasis. The instrument used was the Multidimensional Coping Scale (COPE) of Carver, Scheier and Weintraub (1989), adapted by Cassuso in 1996 and a sociodemographic tab.